Analisis Pendapatan Petani Tomat di Desa Potokullin Kecamatan Buntu Batu Kabupaten Enrekang - Hamka Mastam; Andi Nuddin; Nurhaedah Nurhaedah (Universitas Muslim Maros, 2023)
This study aims to determine the average income of tomato farmers, the amount of production produced by tomato farmers, and the feasibility of tomato farming. the method used in this research is a survey method that aims to obtain a representative picture of a regional situation and to obtain facts that occur in the field through observation, interviews, and documentation. So that the overall state of the area on the economic income of tomato farmers is obtained with data obtained directly from farmers. Based on the results of this study, the average amount earned by tomato farmers was Rp. 9.620.300 per farmer with the income of the respondent farmers being large enough to cover the economic needs of tomato farmers, and the average amount of production produced by tomato farmers was 59,533 per basket. Then the value of the R/C ratio is 3,4 which means that the average number of farmers’ income is greater than the production costs incurred so that the farm is feasible to run in accordance with the provisions of the R/C ratio >1, then the farm is feasible to run.